Aortopexy for Innominate Artery Tracheal Compression in Children. Issue 1 (25th March 2013) - Wine, Todd M.; Colman, Kathryn L.; Mehta, Deepak K.; Maguire, Raymond C.; Morell, Victor O.; Simons, Jeffrey P.
Abstract : Objectives: (1) Evaluate the presentation, diagnostic workup, and outcomes of contemporary surgical intervention for airway obstruction from innominate artery tracheal compression in children. (2) Assess the significance of synchronous airway lesions in the treatment of innominate artery tracheal compression. Study Design: Case series with chart review. Setting: Tertiary care children's hospital. Methods: This study is a retrospective medical record review of 26 consecutive children who underwent aortopexy for innominate artery tracheal compression at a tertiary care children's hospital. Presenting symptoms, diagnostic workup, presence of synchronous airway lesions, length of hospitalization, and treatment outcomes were examined. Results: Twenty‐six patients (17 male, 65%) were included in the study. All were diagnosed with bronchoscopy and confirmed with radiographic imaging. Median age at diagnosis and surgery was 9.7 and 10.0 months, respectively. Presenting symptoms included noisy breathing (93%), cough (78%), dyspnea (44%), apnea (44%), cyanosis (19%), and recurrent respiratory infections (15%). Average degree of tracheal compression was 71% (SD, 12%). Fifteen of 26 (58%) patients had synchronous airway lesions, including mild laryngomalacia and subglottic stenosis. Median length of stay was 2 days. Median follow‐up was 10 months. Subjective improvement occurred in all 21 patients for whom follow‐up information was available. Conclusion: Anterior tracheal vascular compression can cause a variety of airway symptoms. Mild synchronous airway lesions are common and do not prevent successful aortopexy. Aortopexy is a viable treatment option for symptomatic anterior tracheal vascular compression from the innominate artery.